2014
DOI: 10.1136/bcr-2014-203897
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of advanced schistosomiasis: a case of portal vein thrombosis-induced splenomegaly requiring surgery

Abstract: We report for the first time in the Philippines a case of portal vein thrombosis in a 12 year old Filipino boy with advanced schistosomiasis. The boy was referred to the Research Institute for Tropical Medicine (RITM), Manila, due to a rapidly enlarging spleen post-praziquantel treatment. At RITM, liver function tests were within normal limits but complete blood examinations showed pancytopenia and abnormal coagulation times. Serum markers for hepatitis A, B and C were negative. Abdominal MRI revealed schistos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Due to repeated or mass infection of schistosome cercariae, without thorough and timely treatment, patients can evolve into advanced schistosomiasis usually after 2 to 10 years of pathological development process. Clinical symptoms of advanced schistosomiasis include ascites, splenomegaly, portal hypertension, gastro-esophageal variceal bleeding, granulomatous lesions of the large intestine, and serious growth retardation [ 12 , 13 ]. Advanced schistosomiasis japonica is much more common in highly endemic areas, because repeated, heavy exposure to cercariae means that early-stage chronic cases may not be effectively treated in routine control programs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to repeated or mass infection of schistosome cercariae, without thorough and timely treatment, patients can evolve into advanced schistosomiasis usually after 2 to 10 years of pathological development process. Clinical symptoms of advanced schistosomiasis include ascites, splenomegaly, portal hypertension, gastro-esophageal variceal bleeding, granulomatous lesions of the large intestine, and serious growth retardation [ 12 , 13 ]. Advanced schistosomiasis japonica is much more common in highly endemic areas, because repeated, heavy exposure to cercariae means that early-stage chronic cases may not be effectively treated in routine control programs.…”
Section: Introductionmentioning
confidence: 99%
“…Our hypotheses for the probable cause of death is that peripheral blood eosinophilia caused by the parasitic infection promoted a hypercoagulable state that may have resulted in thrombosis leading to ischemia, bowel infarction, and death, which is in line with previous reports with other parasitic infestations [ 26 ]. Although many studies have found an association between the presence of thrombosis in different body sites with different parasitic infections [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], none have directly linked thrombosis with the Enterobius vermicularis infection.…”
Section: Discussionmentioning
confidence: 99%
“…<5% of total cases) that will be encountered in the community. 24 Prior to the commencement of integrated control, it is proposed that the Ministry of Health would sign a written agreement that indigent patients can be sent for appropriate referral, and that all medical expenses will be covered by the government's health-care scheme. 23 The state/provincial government should be lobbied to provide for local travel, and a modest living allowance for the spouse or guardian while the patient is undergoing treatment and recovery.…”
Section: Treatment-annual 60 Mg/kg Pzq + 6 Mg/kg Artmentioning
confidence: 99%